Peningkatan Berkomunikasi dan Hasil Belajar Bahasa Indonesia dengan Strategi Problem Based Learning Di SMA - Suryani, Esti (Manajemen Pendidikan, 2015)
This research  has a purpose  trough BBPL strategic  could improve  communication and Bahasa Indonesia studying result for students X MIA-3 grade semester 2013/2014. This  research  is  a  action  class  research  which  has  two  cyclone  and  each  of  cyclone contain 4 steps, action planning, action doing, observation, and reflection. Subject of this research are the 41 students of X MIA-3 grade SMA Batik 1 Surakarta. Collecting data by  observation  with  observation  sheet  and  written  test  technique  questions  within. Collected data sort by table form graph and analysis. Data analysis in this research used descriptive comparative technique. Total student pass KKM before action are 5 students (19%), first cyclone increase 20 students (49%) and second increase 34 students (85%). Research  result  is  implementation   BPL  strategic  could  improve  communication   and Bahasa   Indonesia   studying   result   persuade   chapter   for  student   X  MIA-3   grade. Summary of this research is implementation  PBL learning strategic in Bahasa Indonesia learning   could  increase   communication   and  Bahasa  Indonesia   studying   result  for students.